Breast fibroadenoma.: Estudio analítico sobre 69 casos - Estellano, Fernando; Bianchi, Gerardo; Laviña, Raúl; Albo, Manuel (Cirugía del Uruguay, 1987)
69 cases of fibroadenoma of the breas! confirmad by pathology study were analyzed. In a 5 years period, in this center were seen 3.000 women. Sorne clinical, diagnostic and therapeutic aspects were analyzed. Abscence of malignan! disease in the serie is pointed out, so is the clinical presentation of breas! cancer masked as fibroadenoma. Considerations about follow up of theese patients are done.